Recovery colleges as enablers of personal recovery: qualitative evaluation of the development of a recovery college in the Netherlands - Thijs Beckers; Martijn Koopmans (BMC Psychiatry)
Abstract Background In the Netherlands, maintaining high standards of mental healthcare faces challenges due to an increasing demand for mental healthcare and a focus on symptomatic recovery rather than personal growth and improvement in the quality of life. Recovery colleges, which emphasize personal recovery through hope, autonomy, and empowerment, offer a transformative approach by fostering an environment where individuals with mental distress can learn and thrive. The aim of this study was to explore the experiences of students and relevant stakeholders (like family members or regional social workers) with the recovery college. Methods This study evaluated the experiences of students working on their personal recovery at the Recovery College Venlo, by utilizing qualitative methods including focus group interviews, personal interviews and thematic analyses. Results The participants reported benefits such as enhanced personal growth and a reduction in self-stigma and reliance on traditional mental health services. Peer workers with lived experience were reported to play a pivotal role in facilitating recovery. Although recovery colleges show promise in supporting personal recovery and providing cost-effective alternatives to conventional mental health services, challenges remain in increasing awareness, accessibility, and family involvement. Further research is needed to optimize the implementation of recovery colleges and fully understand their effectiveness. Conclusions The study underscores the importance of co-creation in the development of recovery-oriented services, and highlights areas for improvement, including enhanced family support and more streamlined access for potential students.